Unlocking the Healing Potential of Natrum Muriaticum in the Treatment of Psoriasis: A Case Report (Advancements in Homeopathic Research, 2025)
The 26-year-old male patient in this case study has chronic psoriasis, which is worse by heat and sun exposure. He primarily presents with erythematous, scaly areas on his back, torso, and forearms. After he went through a period of severe emotional suffering. Natrum muriat- icum, which was chosen based on similarity of symptoms, such as grieving and skin manifes- tations.The patient demonstrated consistent improvement over the course of a three year fol- low-up period, reaching total remission without recurrence. This case report highlights how homoeopathy treats psoriasis holistically by combining physical and mental symptoms. De spite being restricted to a single instance, it shows how homoeopathy can be used to manage chronic illnesses and enhance quality of life.
Keywords: Psoriasis; Natrum muriaticum; Case report; Homoeopathy